HOLISTIC WELLNESS CENTER: URBAN OASIS BASED ON REGENERATIVE ARCHITECTURE IN SURABAYA - Gray Fhayza Anggreina Mahadi; Nurhamdoko Bonifacius; Adisti Safrilia (Architecture Study Program, Faculty Of Engineering, University of Merdeka Malang, 2025)
The increasing demands of urban life in Surabaya, combined with intense workloads, rapid development, and poor work-life balance, have contributed to a significant rise in stress, anxiety, and mental health disorders, particularly among the productive-age population. Reports from the World Health Organization and the 2018 Riskesdas survey indicate that East Java has one of the highest prevalence rates of psychological disorders in Indonesia. Locally, prolonged working hours and toxic workplace environments are recognized as major contributing factors. At the same time, Surabaya holds strong potential in providing environmental and healthsupportive infrastructure. The city has achieved 22% green open space (RTH), exceding the national standard, and demonstrates growing public awareness of wellness and physical fitness. In response to these issues, this project proposes a Holistic Wellness Center as a regenerative urban solution. The design combines facilities for physical and mental well-being such as gym areas, yoga studios, spa, and reflection spaces with regenerative architectural strategies including green building integration, renewable energy systems, grey and black water recycling, and natural ventilation. This project aims to create an inclusive and sustainable facility that not only addresses mental and physical health concerns, but also contributes positively to urban ecological restoration and environmental awareness through regenerative design.